PLANNING FOR THE SMART MOSQUE AS ISLAMIC LEARNING RESOURCES CENTER - - Muhlis; - Sugiyo; Totok Sumaryanto; - Kardoyo (Indonesian Journal of Islamic Literature and Muslim Society, 2016)
The purpose of this research to describe, to analyze, and to develop, the so-called “smart mosque” as a development model for the planning of an integrated Islamic education classroom. The approach of this research is quantitative with survey techniques. Respondents of this survey to all teachers PAI in 31 of senior Islamic high school in Grobogan, Jawa Tengah Indonesia. The taking of data with the questioner.  The Data are analyzed with descriptive analysis. The finding this research of Islamic learning planning at 31 Islamic senior high schools shows 83.9% of them need mosque as laboratory and learning sources. The planning design effectiveness is carried out with practitioner and expert validation with focus group discussion (FGD) pattern and products test on design subject. There are three models for the planning of Islamic education classroom which developed in this study are (1) center model (center of learning resource and center of religious affection)., (2) area model; the area of Qur’an Hadith, Fiqh, Aqidah Akhlaq, and Islamic history), (3) corner model; restroom, locker rooms, stairs, purity/ berwudlu, worship (separate sons and daughters)